Countermeasure to protect sensitive information stealthily in remote interchanges using steganography in educational environments. Issue 2 (April 2021) - Babu, I; Jose, Deepa
Abstract: Nowadays, students of electronics, electrical and computer science engineering are very much curious to know about the various security issues in wireless communication. Therefore, these students require a platform (i.e. by using Matlab software) that can fetch knowledge about the security issues in wireless communication. The Matlab software will give a perfect understanding about the mathematical concepts through a graphical representation. Therefore, students can understand the typical mathematical equation very easily. The main objective of our paper is to create a countermeasure environment that would protect the sensitive information passing through the multi-input and multi-output (MIMO)-OFDM channel. A novel remote steganography method is proposed, and the essential execution of the system was assessed. In this research work, a remote steganography utilizing the MIMO-OFDM structure, the sensitive information processing and also an Eigenbeam-space Division Multiplexing conveyance are proposed. Based on the Matlab simulation results, our proposed technique aims to reduce the bit error rate. In addition, SNR values for different modulation techniques successfully retrieved from the original information are analyzed. And finally, we make two project groups: one is related to the cryptography method and the second group is related to combining the cryptography and steganography methods, and we differentiate which group information is more secure in the wireless communication platform.